IL-27-containing exosomes secreted by innate B-1a cells suppress and ameliorate uveitis - Kang, Minkyung; Yadav, Manoj Kumar; Mbanefo, Evaristus C.; Yu, Cheng-Rong; Egwuagu, Charles E. (Frontiers in Immunology, 2023)
Introduction IL-27 is a heterodimeric cytokine composed of Ebi3 and IL-27p28 and can exert proinflammatory or immune suppressive effects depending on the physiological context. Ebi3 does not contain membrane-anchoring motifs, suggesting that it is a secreted protein while IL-27p28 is poorly secreted. How IL-27p28 and Ebi3 dimerize in-vivo to form biologically active IL-27 is unknown. Major impediment to clinical use of IL-27 derives from difficulty of determining exact amount of bioavailable heterodimeric IL-27 needed for therapy. Methods To understand how IL-27 mediates immune suppression, we characterized an innate IL-27-producing B-1a regulatory B cell population (i27-Breg) and mechanisms i27-Bregs utilize to suppress neuroinflammation in mouse model of uveitis. We also investigated biosynthesis of IL-27 and i27-Breg immunobiology by FACS, immunohistochemical and confocal microscopy. Results Contrary to prevailing view that IL-27 is a soluble cytokine, we show that i27-Bregs express membrane-bound IL-27. Immunohistochemical and confocal analyses co-localized expression of IL-27p28 at the plasma membrane in association with CD81 tetraspanin, a BCR-coreceptor protein and revealed that IL-27p28 is a transmembrane protein in B cells. Most surprising, we found that i27-Bregs secrete IL-27-containing exosomes (i27-exosomes) and adoptive transfer of i27-exosomes suppressed uveitis by antagonizing Th1/Th17 cells, up-regulating inhibitory-receptors associated with T-cell exhaustion while inducing Treg expansion. Discussion Use of i27-exosomes thus obviates the IL-27 dosing problem, making it possible to determine bioavailable heterodimeric IL-27 needed for therapy. Moreover, as exosomes readily cross the blood-retina-barrier and no adverse effects were observed in mice treated with i27-exosome, results of this study suggest that i27-exosomes might be a promising therapeutic approach for CNS autoimmune diseases.